Role of Phytoalexins in Plant-Microbe Interactions and Human Health - Sen, Suman (International Journal of Scientific Research and Management (IJSRM), 2017)
The biochemical basis of defence mechanisms in plants, conferring disease resistance is under active investigation for years. Plants have evolved a broad array of defense mechanisms involved in disease resistance. Synthesis of Phytoalexins is one such mechanism. Phytoalexins are low molecular weight antimicrobial compounds that are produced by plants as a response to biotic and abiotic stresses. As such they take part in an intricate defense system which enables plants to control invading microorganisms. Most of what is known about phytoalexins derives from extensive work on a limited number of plant families. Various pathways are utilized for producing different phytoalexins. Phytoalexins are considerably less toxic than chemical fungicides. Gain- or loss-of-function genetic approaches addressing phytoalexin production for disease resistance have provided direct and indirect proofs of their implication in plant-microbe interactions. Besides that, Phytoalexins have been reported to display healthpromoting effects in humans. A few of them have been reported to exert antioxidant, anti carcinogenic and cardiovascular protective activities